Attitudes towards the use of online Rosetta Stone Platform and Academic performance in Fifth Cycle Students of Environmental Engineering at Alas Peruanas University, Lima, 2018 - Lazo Montero, Gloria Lizeth (2019)
By means of this research we wanted to study about the attitudes towards the use of online Rosetta Stone Platform and Academic performance in Fifth Cycle Students of Environmental Engineering at Alas Peruanas University that took place in the city of Lima in the year 2018.The main objective was to establish the relationship between the variables attitudes and academic performance. This research was of descriptive type and quantitative approach with a correlational design. The method used for this work was the descriptive method. The population and simple were the same 60 Fifth Cycle Students of Environmental Engineering at Alas Peruanas University due to the fact that the population was small. After the corresponding hypothesis testing, we arrived at the conclusion that attitudes towards the use of Online Rosetta Stone Platform are significantly related to academic performance in Fifth Cycle Students of Environmental Engineering at Alas Peruanas University, Lima, 2018. Due to the fact that a Spearman's Rho correlation coefficient = 0,665 ** was obtained, which is interpreted at 99,99% ** the correlation is significant at the bilateral 0,01 level, interpreted as a high positive relationship between the variables, with a p = 0,00 (p <0,01), rejecting the null hypothesis.